2018
DOI: 10.1007/s12134-018-0544-6
|View full text |Cite
|
Sign up to set email alerts
|

West African Immigrant Perspectives on Female Genital Cutting: Experiences, Attitudes, and Implications for Mental Health Service Providers

Abstract: This small pilot study analyzed the experiences of female genital cutting (FGC) among West African immigrants in New York City from three West African countries (the Gambia, Guinea, and Mali) with FGC prevalence rates of 76, 97, and 89%, respectively, among girls and women aged 15 to 49 years. Nine women participated in two focus group sessions. In the first group, five female participants ranged in age from18-20, and in the second, four participants ranged in age from 31 to 44. Focus group data were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 27 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…Slow-onset hazards can cut off and considerably limit the access to medical services and education, especially in underserviced areas. Women and children in vulnerable situations face the greatest and disproportionate risks from the negative effects of climate change, which can expand gender inequalities [69,70]. These women face the inequality of accessing the human social freedoms and means necessary for the realization of social, economic, and cultural rights, which can cause losses in times of environmental pressure.…”
Section: The Link Between Slow-onset Events and The Vulnerability Of mentioning
confidence: 99%
“…Slow-onset hazards can cut off and considerably limit the access to medical services and education, especially in underserviced areas. Women and children in vulnerable situations face the greatest and disproportionate risks from the negative effects of climate change, which can expand gender inequalities [69,70]. These women face the inequality of accessing the human social freedoms and means necessary for the realization of social, economic, and cultural rights, which can cause losses in times of environmental pressure.…”
Section: The Link Between Slow-onset Events and The Vulnerability Of mentioning
confidence: 99%
“…Vacation cutting was discussed in six studies [31, 36, 37, 42, 44, 53]. Overall, these studies found women were opposed to vacation cutting.…”
Section: Resultsmentioning
confidence: 99%
“…In two studies, women discussed fears and feeling pressure from family to take their daughters to their home countries where they would be at risk of undergoing FGM/C without maternal consent [31, 37]. In one study, women discussed having been informed by medical providers that if their daughters had FGM/C after returning from a trip to Africa, there would be legal consequences [37]. In two studies, women reported that they were aware of instances where daughters were sent back for FGM/C [37, 44].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations